Burnout among public primary school teachers in Dire Dawa administrative region, Ethiopia - Mamo, Daniel (Frontiers in Education, 2022)
The major purpose of the study was to assess the level of professional burnout among government-owned primary school teachers in Dire Dawa town. In addition, the study assessed the effect sociodemographic variables have on the professional burnout of primary school teachers in Dire Dawa town. To this end, a cross-sectional survey research design was preferred. Whereas 15 primary schools were selected purposively, 211 teachers from these schools were selected using a simple random sampling technique. Data was collected using a teacher burnout scale developed by Seidman & Zager (1987) with four major dimensions: career satisfaction, coping with job stress, perceived administrator support, and attitude towards students. The analysis of the collected data was carried out using descriptive statistics, Spearman rho correlation, and logistic regression. The findings of the study revealed that primary school teachers in the region experience high professional burnout with means of 2.65, 2.64, 2.64, and 2.75 for career satisfaction, perceived administrative support, coping with job-related stress, and attitude towards students. The analysis also revealed that male teachers experience more burnout than female teachers do. Contrary to the extant literature, younger male teachers are less prone to experience burnout than their older counterparts are. Besides, experienced teachers are more likely to experience burnout than their less experienced counterparts are. However, educational qualification showed no relationship with the experience of burnout among primary school teachers. On the other hand, teachers’ gender (male) is correlated with career satisfaction and coping with job stress with a correlation coefficient of 0.249 and -0.190, while experience is correlated with perceived administrative support and attitude towards students with a correlation coefficient of -.423 and -.332, all significant at p<0.05 level of confidence. In addition, the logistic regression analysis revealed that 12% of the change in burnout experience of primary schoolteachers’ could be explained by socio-demographic variables. Thus, it was recommended that the education bureau and school leaders at primary school levels should introduce urgent interventions to help teachers cope with their job stress and burnout.